Main psychometric evaluation methods of the validity of measuring instruments - Cunha, Cristiane Martins; de Almeida Neto, Omar Pereira; Stackfleth, Renata (Journal of Health Care, 2016)
Introduction: The publication of studies demonstrating the importance of proper psychometric evaluationof measuring instruments as a good quality instrument criterion with regard to evidence of validityand reliability is increasingly common. The validity of a measuring instrument brings together a body ofevidence proving that it is in fact measuring the construct that it is supposedly measuring. This articleaims to present the basic principles of psychometric evaluation of the validity of measuring instrumentsand the main statistical methods described in the literature. Development: The survey was conductedfrom publications in MEDLINE, LILACS, and IBECS databases and also from the descriptions in relatedbooks. The studies’ analyses involved reading titles, abstracts, and articles published in the last 10 years andduplicated articles or those not responding to the purpose of this review were excluded. The techniques ofevaluation of quantitative validity that make up the trinary model (construct validity, content validity, andcriterion validity) has proved sufficient and satisfactory in demonstrating the validity of an instrument.Conclusion: In general, the authors agree with the basic criteria for evaluating the validity of a good measuringinstrument. The validity of a measuring instrument is an existing psychometric attribute in a goodinstrument and needs to be covered in these study categories.